Natural convection of Al2O3/H2O nanofluid in a cavity with a heat-generating element. Heatline visualization - Bondarenko, Darya S.; Sheremet, Mikhail A.; Öztop, Hakan Fehmi; Ali, Mohamed E. (Pergamon-Elsevier Science Ltd, 2019)
Cooling of electronic devices is a very important topic. The present paper deals with numerical simulation of natural convection cooling of heat-conducting and heat-generating source using an alumina-water nanofluid under the effect of cold vertical walls. Governing equations formulated in dimensionless stream function, vorticity and temperature variables have been solved by the finite difference method. The effects of nanoparticles concentration, heat source location, internal heat generation flux and heat source material on fluid flow and heat transfer have been studied. It has been found that an addition of nanoparticles can intensify the cooling process when the heat is located near the vertical cold wall. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Natural convection; Nanofluid; Heat-generating source; Heatlines; Square cavity; Finite difference method